1999
DOI: 10.1017/s0029665199000907
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and immunity in the elderly

Abstract: Immune function declines with age, leading to increased infection and cancer rates in aged individuals. In fact, recent progress in the study of immune ageing has introduced the idea that rather than a general decline in the functions of the immune system with age, immune ageing is mainly characterized by a progressive appearance of immune dysregulation throughout life. Changes appear earlier in life for cell-mediated immunity than for humoral immunity. Thus, agerelated modifications in cell-mediated immunity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
129
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 82 publications
4
129
0
1
Order By: Relevance
“…In has been suggested that enhanced innate immunity may occur with age as a countermeasure against declining CMI. In particular, numerous studies have reported increased numbers of NK cells (irrespective of the surface marker used to characterise them) with advancing age (for reviews, see Lesourd & Mazari, 1999;Mocchegiani & Malavolta, 2004). Preservation of NK cell cytotoxicity and numbers in middle age may be crucial in preventing the development of some age-related diseases and achieving successful ageing; it has been demonstrated that NK cell function is the only parameter in the healthy elderly to be negatively correlated with a severe history of infection or subsequent death owing to infection (Ogata et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In has been suggested that enhanced innate immunity may occur with age as a countermeasure against declining CMI. In particular, numerous studies have reported increased numbers of NK cells (irrespective of the surface marker used to characterise them) with advancing age (for reviews, see Lesourd & Mazari, 1999;Mocchegiani & Malavolta, 2004). Preservation of NK cell cytotoxicity and numbers in middle age may be crucial in preventing the development of some age-related diseases and achieving successful ageing; it has been demonstrated that NK cell function is the only parameter in the healthy elderly to be negatively correlated with a severe history of infection or subsequent death owing to infection (Ogata et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies examining zinc status and immune function have focused on infectious disease in childhood (Bahl et al, 1998;Black, 2003;Wieringa et al, 2004) and the elderly (Bogden et al, 1988;Prasad et al, 1993;Ravaglia et al, 2000;Bogden, 2004;Lesourd, 2004). There is a distinct lack of studies that have investigated the age-related changes in immune function in the late-middle-aged population (55-70 y), or indeed that have assessed zinc status of this age group.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports (9,12,13,15,17-19,20 22,23,30) give highly variable results on NK cytotoxic activity ( Table 2). The role played by the neuroendocrine immune network and/or by nutritional factors in the maintenance of NK cell functions in ageing has also been widely discussed (20,(31)(32)(33).…”
Section: Effect Of Feeding On Nk Functions In Healthy Elderly Peoplementioning
confidence: 99%
“…Similarly, there is strong evidence that undernutrition induces immunodeficiency. Several reports (18,34) provide evidence that human immune ageing is strongly influenced by nutritional factors, mainly low nutritional diet in either macro-or micronutrients. Our data also show an increasing capacity of NK cells to kill target cells.…”
Section: Effect Of Feeding On Nk Functions In Healthy Elderly Peoplementioning
confidence: 99%
“…Although some experimental studies have suggested that the use of arginine as a supplement leads to clinical benefits in critically ill patients (Muhling et al, 2002;Lesourd, 2004), there is a lack of studies about the potential benefits of any nutrients supplementation after pneumococcal immunization of older persons, free-living in the community. Considering the individual variation in the immune response to pneumococcal vaccine and the reported benefits of arginine supplementation for immune function, this study intended to verify whether or not oral arginine supplementation affects the humoral response against the pneumococcal polysaccharide vaccine and some variables of the innate immune response in a group of persons aged 60 y and older, living in the community.…”
Section: Introductionmentioning
confidence: 99%